Assessment of tubercle bacilli in various organs by staining and polymerase chain reaction technique - Raja, Minali; ., Tanvi (International Journal of Advances in Medicine, 2018)
Background: Early diagnosis of tuberculosis (TB) by different clinical methods plays a major role in control of TB in early stages. The present study was done with the aim to assess and compare the efficiency of staining techniques and polymerase chain reaction (PCR) for detection of tubercle bacilli in various organs. Methods: The study included data 14,472 patients of both prospective (during March 2008 to 2009) and retrospective cases (past one year of the study period). For prospective cases the cytological material for the study was collected by fine needle aspiration cytology (FNAC). For retrospective cases of past one year were retrieved from the records. TB suspected cases were evaluated by Ziel-Nelson (ZN), Auramine-Rhodamine (A-R) staining techniques and by PCR. Results: Total 284 cases were diagnosed with TB in various organs. In them, epithelioid granuloma was seen 227 cases (79.92%) and Langhans giant cells were seen in 18 cases (6.34%). AFB positivity on ZN staining was observed in 161 cases (56.69%) and 9 cases (3.16%) showed positivity for tubercle bacilli on A-R staining. PCR was done in 20 prospective cases and total percentage of positivity by PCR was seen in 18 cases (90%). Conclusions: The total percentage positivity for detection of tubercule bacilli by PCR assay was found to be more (90%) with high sensitivity and specificity compared to ZN (56.6%) and AR staining techniques (3.16%).